Signaling via TLR2 and TLR4 Directly Down-Regulates T Cell Effector Functions: The Regulatory Face of Danger Signals - Cohen, Irun R.; Zanin-Zhorov, Alexandra (Frontiers in Immunology, 2013)
Toll-like receptors (TLRs) are widely expressed and play an essential role in the activation of innate immune cells. However, certain TLRs are also expressed on T cells, and TLR ligands can directly modulate T cell functions. Here, we discuss findings indicating that T cells directly respond to Heat Shock Protein (HSP) 60, a self molecule, or to the HSP60-derived peptide, p277, via a TLR-2-dependent mechanism. HSP60 has been considered to be a “danger signal” for the immune system because of its ability to induce pro-inflammatory phenotypes in innate immune cells – in this case via TLR-4 activation; nevertheless, TLR-2 engagement by HSP60 on T cells can lead to resolution of inflammation by up-regulating the suppressive function of regulatory T cells and shifting the resulting cytokine secretion balance towards a Th2 phenotype. Moreover, T-cell TLR-4 engagement by LPS leads to up-regulation of SOCS3 expression and consequently down-regulates T cell chemotaxis. Thus, TLR2 and TLR4 activation can contribute to both induction and termination of effector immune responses by controlling the activities of both innate and adaptive immune cells.